Analisis Yuridis Atas Praktik Komersialisasi Foto Tanpa Izin Objek oleh Fotografer dalam Perspektif Maqashid Syariah - Mahatir Harahap; Tetty Marlina Tarigan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of digital technology has had a significant impact, including increasing violations of privacy rights in public areas. One form of violation that often occurs is the practice of taking and using photographs without the object's consent. This action has the potential to violate moral and economic rights as stipulated in Law Number 28 of 2014 concerning Copyright, especially if the photo is used for commercial purposes without permission. Furthermore, this practice also contradicts the principle of personal data protection as stipulated in Law Number 27 of 2022 concerning Personal Data Protection. This study aims to analyze the form of legal protection for photographed objects in the practice of taking photographs without permission under Indonesian positive law and to review it from the perspective of maqāṣid shari'ah. This research is a normative legal research using a statute approach and a conceptual approach. Legal materials were obtained through literature studies and analyzed descriptively using deductive reasoning methods. The results of the study indicate that the practice of taking photographs without the object's permission in the Indonesian legal system contains two dimensions of legal violations: violation of copyright and violation of the right to privacy or personal data. From the perspective of the maqāṣid shari'ah (Islamic principles), this practice contradicts the principles of ḥifẓ al-māl (protection of property) and ḥifẓ al-nafs (protection of life), because the unauthorized use of photographs for commercial purposes constitutes a form of appropriation of the economic and moral rights of others, potentially leading to injustice.